Evaluation of the toxicity and repellency of tropical plant extract against subterranean termites, Globitermes sulphureus and Coptotermes gestroi - Noor Hazwani, Bakaruddin; Hamady, Dieng; Shaida Fariza, Sulaiman; Abdul Hafiz, Ab Majid (Elsevier Ltd., 2018)
The harmful effects of chemical-based termiticides and the increased incidence of termite resistance have resulted in the need for safer and more effective termiticides. Therefore, the screening of antitermiticidal activity of naturally-occurring products could possibly hamper an alternative means in termite control strategies. The aims of this study were to determine the toxicity and repellency of L. leucocephala, A. paniculata, Az. indica and P. niruri crude extracts against two subterranean termites, G. sulphureus and C. gestroi. Bioassays were conducted by applying varying concentrations of the plant extracts (10,000 ppm, 5000 ppm and 500 ppm) on both termite species under laboratory conditions. All extracts exhibited a significant antitermiticidal activity in time- and concentration-dependent manners after 14 days of exposure. The highest mortality of G. sulpureus and C. gestroi were noted in all methanolic extracts of P. niruri, L. leucocephala, A. paniculata, Az. indica at 10,000 ppm. High repellent activity was also noted in the choice bioassay when both termites were treated with all methanolic extracts at 10,000 ppm. © 2018 China Agricultural University